DNA prime-protein boost based vaccination with a conserved region of leptospiral immunoglobulin-like A and B proteins enhances protection against leptospirosis - Karine M Forster; Daiane D Hartwig; Thaís L Oliveira; Kátia L Bacelo; Rodrigo Schuch; Marta G Amaral; Odir A Dellagostin (Memorias do Instituto Oswaldo Cruz, 2015)
Leptospirosis is a zoonotic disease caused by pathogenic spirochetes of theLeptospira genus. Vaccination with bacterins has severe limitations. Here, we evaluated the N-terminal region of the leptospiral immunoglobulin-like B protein (LigBrep) as a vaccine candidate against leptospirosis using immunisation strategies based on DNA prime-protein boost, DNA vaccine, and subunit vaccine. Upon challenge with a virulent strain ofLeptospira interrogans, the prime-boost and DNA vaccine approaches induced significant protection in hamsters, as well as a specific IgG antibody response and sterilising immunity. Although vaccination with recombinant fragment of LigBrep also produced a strong antibody response, it was not immunoprotective. These results highlight the potential of LigBrep as a candidate antigen for an effective vaccine against leptospirosis and emphasise the use of the DNA prime-protein boost as an important strategy for vaccine development.